2018
DOI: 10.1371/journal.pone.0195103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating pre-pregnancy dietary diversity vs. dietary quality scores as predictors of gestational diabetes and hypertensive disorders of pregnancy

Abstract: BackgroundDietary diversity scores (DDS) are considered as metrics for monitoring the implementation of the UN’s Sustainable Development Goals, but they need to be rigorously evaluated.ObjectiveTo examine two DDS, the Food Groups Index (FGI), and the Minimum Dietary Diversity-Women (MDD-W), alongside two dietary quality scores, the Alternate Healthy Eating Index (AHEI-2010) and the Prime Diet Quality Score (PDQS), with risks of gestational diabetes mellitus (GDM) and hypertensive disorders of pregnancy (HDPs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 43 publications
2
81
1
1
Order By: Relevance
“…Prime Diet Quality Score The Prime Diet Quality Score (PDQS) (23,24) is a food-based, twenty-one-component, dietary score consisting of twelve 'adequacy', seven 'moderation' and two populationspecific components (for adults, only low-fat dairy foods are coded as an adequacy component, while high-fat dairy and eggs are not coded). The score was developed and successfully evaluated by comparison with a comprehensive FFQ in a high-income country setting (23,24) . In two studies of US women, higher score on the PDQS was found to predict lower risk of CHD (23) and gestational diabetes mellitus (24) .…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Prime Diet Quality Score The Prime Diet Quality Score (PDQS) (23,24) is a food-based, twenty-one-component, dietary score consisting of twelve 'adequacy', seven 'moderation' and two populationspecific components (for adults, only low-fat dairy foods are coded as an adequacy component, while high-fat dairy and eggs are not coded). The score was developed and successfully evaluated by comparison with a comprehensive FFQ in a high-income country setting (23,24) . In two studies of US women, higher score on the PDQS was found to predict lower risk of CHD (23) and gestational diabetes mellitus (24) .…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Dietary pattern analysis has become a popular tool for exploring dietary associations with GDM, as it is thought to better reflect real eating behaviours by considering the eating pattern as a whole [24]. A number of studies have found dietary patterns characterised by high intakes of red and processed meats, fried foods and added sugars to be associated with an increased risk of GDM, while dietary patterns characterised by high consumption of fruit, vegetables, wholegrains and nuts or 'Mediterranean'-style dietary patterns to be associated with a lower risk of developing GDM [25][26][27][28][29][30][31][32][33][34][35]. Nonetheless, research of dietary patterns and risk of GDM has primarily been conducted in largely Caucasian populations [11,25,30,34,36], with many using data from the same cohort of women from the Nurses' Health Study II [25,28,36].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analyzed the association between adherence to a MD, or other dietary compositions during pregnancy, and GDM development [19,20,21,22,23,24], yet few have assessed the relationship between pre-pregnancy adherence to a MD and the development of GDM. Those that do have inconsistent results and show a less clear association, which may be due to the fact that some of these studies have been carried out on the MD in non-Mediterranean populations [25,26,27] or with different anthropometric, sociodemographic characteristics and culinary habits [19,20,21,22,23,24,25,26,27,28]. Thus, this association has not yet been demonstrated consistently or conclusively.…”
Section: Introductionmentioning
confidence: 99%